Exploring patient-reported outcomes of home-based cardiac rehabilitation in relation to Scottish, UK and European guidelines: an audit using qualitative methods. Issue 12 (16th December 2018) - Ranaldi, Hannah; Deighan, Carolyn; Taylor, Louise
Abstract : Objectives: The Heart Manual (HM) is the UK's leading facilitated home-based cardiac rehabilitation (CR) programme for individuals recovering from myocardial infarction and revascularisation. This audit explored patient-reported outcomes of home-based CR in relation to current Scottish, UK and European guidelines. Setting: Patients across the UK returned their questionnaire after completing the HM programme to the HM Department (NHS Lothian). Participants: Qualitative data from 457 questionnaires returned between 2011 and 2018 were included for thematic analysis. Seven themes were identified from the guidelines. This guided initial deductive coding and provided the basis for inductive subthemes to emerge. Results: Themes included: (1) health behaviour change and modifiable risk reduction, (2) psychosocial support, (3) education, (4) social support, (5) medical risk management, (6) vocational rehabilitation and (7) long-term strategies and maintenance. Both (1) and (2) were reported as having the greatest impact on patients' daily lives. Subthemes for (1) included: guidance, engagement, awareness, consequences, attitude, no change and motivation. Psychosocial support comprised: stress management, pacing, relaxation, increased self-efficacy, validation, mental health and self-perception. This was followed by (3) and (4). Patients less frequently referred to (5), (6) and (7). Additional themes highlighted the impact of the HM programme and that patients attributed the greatest impact to a combination of all the above themes. Conclusions: This audit highlighted the HM as comprehensive and inclusive of key elements proposed by Scottish, UK and EU guidelines. Patients reported this had a profound impact on their daily lives and proved advantageous for CR.